1993
DOI: 10.1016/0735-1097(93)90053-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial of percutaneous peripheral ultrasound angiopalsty

Abstract: Our findings indicate that percutaneous peripheral ultrasound angioplasty 1) is useful for recanalization of fibrous, calcific and thrombotic arterial occlusions; 2) reduces arterial stenoses; and 3) has clinical and ankle-brachial index data indicative of a restenosis rate of 20% at 6 to 12 months in a small cohort of patients. A larger randomized series of patients will need to be studied to assess the impact of ultrasound ablation on restenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…A more recent report 27 showed a small acceleration of whole-blood clot lysis with urokinase in combination with 170-kHz ultrasound at 0.5 W/cm 2 . A catheter-mounted transducer at 225 kHz accelerated thrombolysis with urokinase in vitro, 20 as did a 20-kHz catheter-mounted transducer. 25 The latter demonstrated enhancement of fibrinolysis with 20-kHz ultrasound at intensities of 1 and 1.5 W/cm 2 and reported up to 40% "fibrinolysis" that may have represented mechanical clot disruption.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent report 27 showed a small acceleration of whole-blood clot lysis with urokinase in combination with 170-kHz ultrasound at 0.5 W/cm 2 . A catheter-mounted transducer at 225 kHz accelerated thrombolysis with urokinase in vitro, 20 as did a 20-kHz catheter-mounted transducer. 25 The latter demonstrated enhancement of fibrinolysis with 20-kHz ultrasound at intensities of 1 and 1.5 W/cm 2 and reported up to 40% "fibrinolysis" that may have represented mechanical clot disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that US can accelerate fibrinolysis in vivo, but they differ from our findings in several respects. In some reports, thrombi were mechanically disrupted in vitro 22,23 or in animal models 23,24 with wires vibrating at US frequencies in the absence of plasminogen activator, and this approach has been tested in small studies in patients with coronary 25 or peripheral 26,27 arterial occlusion and with occluded coronary bypass grafts. 28 This treatment requires endovascular positioning of the wire, and it can result in vessel wall damage, excessive heating, and distal embolization of clot fragments.…”
Section: Suchkova Et Al Ultrasound Increases Thrombolysis and Perfusionmentioning
confidence: 99%
“…The mechanical effect this form of ultrasound has on biological tissues was first noted by Conte and de Lorenzi (cited in Atar et al (27)) and its effectiveness is based on the fact that at the right combination of frequency and amplitude inelastic rigid tissue is vigorously disrupted while elastic tissue can absorb the energy (28,29).…”
Section: Iiia Backgroundmentioning
confidence: 99%
“…Siegel et al (29) experimentally tested a 19.5 kHz system on 50 lesions of which 34% were calcified. The results showed that ultrasound delivered via a wire waveguide could recanalise the arteries affected by the lesions and that the calcified arteries treated with therapeutic ultrasound could subsequently be dilated at lower pressures than before suggesting an overall increase in the distensibility of the lesion.…”
Section: Vc Prototypes and Clinical Devicesmentioning
confidence: 99%
See 1 more Smart Citation